The Triplet Hydroxyl Radical Complex of Phosphorus Monoxide. Issue 49 (19th October 2020) - Chu, Xianxu; Qian, Weiyu; Lu, Bo; Wang, Lina; Qin, Jie; Li, Jun; Rauhut, Guntram; Trabelsi, Tarek; Francisco, Joseph S.; Zeng, Xiaoqing
Abstract: Phosphorus monoxide ( . PO) is a key intermediate in phosphorus chemistry, and its association with the hydroxyl radical ( . OH) to yield metaphosphorous acid ( cis ‐HOPO) contributes to the chemiluminescence in the combustion of phosphines. When photolyzing cis ‐HOPO in an Ar‐matrix at 2.8 K, the simplest dioxophosphorane HPO2 and an elusive hydroxyl radical complex (HRC) of . PO form. This prototypical radical‐radical complex reforms into cis ‐HOPO at above 12.0 K by overcoming a barrier of 0.28±0.02 kcal mol −1 . The vibrational spectra of this HRC and its D‐ and 18 O‐isotopologues suggest a structure of . OH⋅⋅⋅OP ., for which a triplet spin multiplicity with a binding energy of −3.20 kcal mol −1 has been computed at the UCCSD(T)‐F12a/aug‐cc‐pVTZ level. Abstract : A triplet radical‐radical complex consisting of a hydroxyl radical and phosphorus monoxide ( . OH⋅⋅⋅OP . ), which serves as an important intermediate in the combustion of phosphines, has been captured in solid Ar‐matrices at 2.8 K. Its interconversion with metaphosphorous acid ( cis ‐HOPO) has also been observed.